Simulação acústica de espectros sonoros e barreiras em subestação de energia - Silva, Mateus da (2022)
Electric power substations are increasingly inserted in urban environments, making the noise generated by power transformers a recurring discomfort for the population. In order to improve social welfare, two studies were carried out through acoustic simulations, the first being the evaluation of the simulation program tools and other types of noise spectra generated by transformers, thus seeking ways to evaluate the noise. before installing the equipment in a substation to be built and also the possibility of simulating a substation without the need for onsite measurements. The second stage of the study sought, through acoustic simulations, to verify the effectiveness of different geometries of acoustic barriers in mitigating the sound pressure level in homes close to a substation. In order to guarantee a correct simulation, data referring to the noise generated by the transformers in a real substation were collected, both for the purposes of noise characterization and for data referring to the sound pressure level in the substation region. With this, the real values were compared with the simulated values, and later the sound mitigation capacity was simulated with the insertion of acoustic barriers. Such barriers could influence the form of noise dispersion depending on its proximity to the source, its geometry and height. Among the 4 forms of simulated barriers, values from 3 to 17 dB(A) of loss by insertion of barriers were found. During the evaluation of the spectra, which were obtained through the simulation software and the literature, it was possible to verify that the spectrum generated by the software presented values that were too high and therefore unreliable. The spectrum found in the literature presented plausible values, however its use is restricted, since the variations presented between it and the real spectrum had values of up to 8.6% of difference.